Mechanism and effectiveness of natamycin produced by Streptomyces philanthi RL-1-178 in controlling green mold disease caused by Penicillium digitatum on postharvest mandarin fruit (Citrus reticulata Blanco) - Sawai Boukaew; Krittin Chumkaew; Sirasit Srinuanpan (Journal of Agriculture and Food Research)
Natamycin, also known as pimaricin, has been widely used as an antimycotic agent in the food industry. This study evaluates the potential of natamycin produced by Streptomyces philanthi RL-1-178 as a control agent against green mold disease caused by Penicillium digitatum. Its efficacy is compared with that of sodium benzoate, sodium propionate, Prochloraz®, and Propiconazole®, both in vitro and on mandarin fruit (Citrus reticulata Blanco). In vitro results demonstrated that natamycin was tested across a range of concentrations (16, 32, 64, 128, 256, and 512 μg/mL) and was effective at concentrations as low as 16 μg/mL, with complete inhibition of pathogen growth and spore germination observed at a minimum inhibitory concentration (MIC) of 256 μg/mL. This efficacy was comparable to that of sodium benzoate (2,000 μg/mL), Prochloraz® (500 μg/mL), and Propiconazole® (500 μg/mL). When applied at twice the MIC, natamycin effectively controls P. digitatum, with preventive applications proving more effective than curative ones. However, its curative efficacy was less than that of the tested fungicides, Prochloraz® and Propiconazole®, which achieved complete disease suppression even when applied after pathogen inoculation. Further research indicated that treating fungal spores with natamycin for 12 h before inoculating mandarin fruit prevented visible disease symptoms, demonstrating strong preventive capabilities. Significant disruptions in ergosterol biosynthesis and impairments in both enzymatic (superoxide dismutase, catalase) and non-enzymatic (oxidized and reduced glutathione, and their ratio) antioxidant defense mechanisms in P. digitatum cells post-treatment indicate the plasma membrane as a key target for its antifungal action. Additionally, natamycin compromised the integrity of the plasma membrane. Overall, our findings demonstrate the efficacy of natamycin in controlling green mold disease, suggesting its potential as a low-toxicity alternative to chemical fungicides for managing postharvest diseases. The study also highlights the use of natamycin produced by S. philanthi RL-1-178 as a biocontrol agent, offering a viable approach for postharvest disease management.